2018
DOI: 10.1136/bmjopen-2018-023445
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric postdischarge mortality in developing countries: a systematic review

Abstract: ObjectivesTo update the current evidence base on paediatric postdischarge mortality (PDM) in developing countries. Secondary objectives included an evaluation of risk factors, timing and location of PDM.DesignSystematic literature review without meta-analysis.Data sourcesSearches of Medline and EMBASE were conducted from October 2012 to July 2017.Eligibility criteriaStudies were included if they were conducted in developing countries and examined paediatric PDM. 1238 articles were screened, yielding 11 eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 31 publications
4
93
1
Order By: Relevance
“…However, children with cSAM experience a high rate of mortality and readmission in the months following hospital discharge especially in sub-Saharan Africa (Berkley et al, 2016;Chhibber et al, 2015;Dubray et al, 2008;Kerac et al, 2009;Moisi et al, 2011;Ngari et al, 2017;Trehan et al, 2013;Veirum, Sodeman, Biai, Hedegård, & Aaby, 2007;Wiens et al, 2013;Wiens et al, 2015). Recent systematic reviews reported paediatric post-discharge mortality rates in resource-poor countries of up to 18% that may exceed in-hospital mortality rates in many settings (Nemetchek et al, 2018;Wiens et al, 2013). Further, postdischarge relapse is poorly defined and infrequently systematically measured in programmes, and therefore less understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, children with cSAM experience a high rate of mortality and readmission in the months following hospital discharge especially in sub-Saharan Africa (Berkley et al, 2016;Chhibber et al, 2015;Dubray et al, 2008;Kerac et al, 2009;Moisi et al, 2011;Ngari et al, 2017;Trehan et al, 2013;Veirum, Sodeman, Biai, Hedegård, & Aaby, 2007;Wiens et al, 2013;Wiens et al, 2015). Recent systematic reviews reported paediatric post-discharge mortality rates in resource-poor countries of up to 18% that may exceed in-hospital mortality rates in many settings (Nemetchek et al, 2018;Wiens et al, 2013). Further, postdischarge relapse is poorly defined and infrequently systematically measured in programmes, and therefore less understood.…”
Section: Introductionmentioning
confidence: 99%
“…1740 (30) 506 (22) 936 (42) 68 (15) 95 3739 4418 (22) 78 ( (30) 566 (25) 757 (34) 165 (37) 81 3227 3116 (20) 97 (28) Information NA 509 (9) 211 (9) 176 (8) 30 730 127 813 1642 (12) Ethnicity, n (%) Brahmin and Chhetri 2573 (45) 944 (41) 1072 (48)…”
Section: Resultsmentioning
confidence: 99%
“…Early discharge from hospital against medical advice is signi cantly associated in Bangladesh as in other developing countries with higher post-discharge mortality and re-admission [4,6,37]. In line with a previous study conducted at icddr,b hospitals [4], we found that mothers who were taking their children home against medical advice were doing so for a range of inter-related reasons, including a view that the child had either recovered enough to go home (ie the child's condition was improving or he/she had recovered from the primary illness), or was not going to recover and so should be taken home.…”
Section: Discussionmentioning
confidence: 99%